PERAN AFEKSI DISPOSISIONAL DALAM MEMPENGARUHI PERILAKU INDIVIDU DALAM ORGANISASI (Fokus Ekonomi, 2008)
Debate the role of affection dispositional in influencing behavior of individual still be discussed, as does written by Davis-Blake, A., & Pfeffer, J. ( 1989) which believes that contribution of affection situational at behavior of individual, and questions the role of affection dispositional at behavior of individual. This article is to be more comprehends position of affection dispositional at position of individual, here in after will influence behavior of individual in organization and finally can give satisfaction at individuals in organization.   Key words: affection dispositional, affection situational, behavior of individual